Tightening techniques for the retaining screws of universal abutment - REGALIN,Alexandre Wittcinski (2016)
Abstract Purpose This study evaluated the torque maintenance of universal abutment retaining screws using different tightening techniques, and coated or uncoated screws. Material and method The screws were tightened to implants as following: Control – 32 Ncm torque; H20 – holding 32 Ncm torque for 20 s; R – 32 Ncm torque, repeated after 10 min (retorque); and H20+R – combining the two tightening techniques. Titanium and coated screws were also evaluated. Result Statistical analysis showed higher maintained torque for titanium screws (p<0.001). The H20+R technique showed the highest maintained torque (p=0.003), but the H20 technique’s maintained torque was similar. Conclusion Titanium screws associating the two tightening techniques can improve maintained torque.